ON IMPROVING THE LEGISLATION ON INSOLVENCY (BANKUPTCY) OF A CITIZEN - L. M. Faizrakhmanova (Russian Journal of Economics and Law, 2013)
Objective: To study and prove the necessity to create an institution of physical person’s bankruptcy in Russia. Methods: Comparative-legal and descriptive methods, as well as systemic-structural method. Results: Analysis is made of legislation of a number of countries on regulating physical persons’ insolvency in order to determine the purposefulness and possibility to introduce insolvency procedures in Russia. The main provisions of a draft law “On rehabilitation procedures implemented to a debtor citizen” are analyzed. The reasons are grounded of the necessity to adopt legislation on regulation of physical persons’ bankruptcy in Russia. Scientific novelty: Positive and negative sides of a draft law “On rehabilitation procedures implemented to a debtor citizen” are revealed, as well as prospects and ways of improving legislation on physical persons’ (citizens’) bankruptcy in Russia. Practical value: Possibility and necessity to solve the problems of citizens’ debts in a civilized way by creating a new environment of interrelations between creditors and debtors for regulating the debts. Physical persons’ bankruptcy should become the institution which would aloe people to satisfy the demands of creditors without violating other people’s interests.